2016
DOI: 10.1016/j.math.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on the most useful physical examination tests used by physiotherapists for patients with headache: A Delphi study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 80 publications
2
59
0
7
Order By: Relevance
“…The subgroup of migraine sufferers identified within the RF model were younger and had a lower JPSE in cervical rotation, greater cervical mobility in rotation and flexion, lower FRT scores (positive), positive PAIVMs reproducing migraine symptoms, normal PPTs over the tibialis anterior, a shorter migraine history, and a lower cranio-vertebral angle while standing as compared to other migraine intensity subgroups. The association of these variables with migraine is not new, since some previous studies have investigated the presence of cervical musculoskeletal disorders in this population, [20][21][22][23][24][25] although their association is still questioned. In fact, a recent meta-analysis concluded that, among several cervical spine musculoskeletal impairments, individuals with migraine exhibit minimally reduced CROM with no differences in head posture or JPSE as compared to headache-free people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subgroup of migraine sufferers identified within the RF model were younger and had a lower JPSE in cervical rotation, greater cervical mobility in rotation and flexion, lower FRT scores (positive), positive PAIVMs reproducing migraine symptoms, normal PPTs over the tibialis anterior, a shorter migraine history, and a lower cranio-vertebral angle while standing as compared to other migraine intensity subgroups. The association of these variables with migraine is not new, since some previous studies have investigated the presence of cervical musculoskeletal disorders in this population, [20][21][22][23][24][25] although their association is still questioned. In fact, a recent meta-analysis concluded that, among several cervical spine musculoskeletal impairments, individuals with migraine exhibit minimally reduced CROM with no differences in head posture or JPSE as compared to headache-free people.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination included the musculoskeletal impairments most commonly associated with patients with headache: cervical flexion‐rotation test (FRT) scores, active range of cervical motion, forward head posture, passive accessory intervertebral movements with head pain reproduction, and JPSE.…”
Section: Methodsmentioning
confidence: 99%
“…Zur Indikationsstellung wird genügend Zeit für eine ausführliche Untersuchung benötigt. Die Befundung orientiert sich an den empfohlenen Assessments für Kopfschmerz-Patienten [12]. Getreu dem Konzept "Hilfe zur Selbsthilfe" sollten passive Maßnahmen zur Muskeldetonisierung und Mobilisation nur eingesetzt werden, wenn eine Indikation hierfür besteht.…”
Section: Indikationsstellungunclassified
“…Die Physiotherapie sollte demnach auf einem ausführlichen Assessment beruhen (z. B. nach Lüdtke) [21] und sich auch konsequent danach richten. Patienten mit langer Krankenanamnese, vielen gescheiterten Therapieversuchen sowie relevanter Komorbidität werden im Rahmen einer 5-tägigen intensivierten ambulanten Versorgung betreut (Modul 2).…”
Section: Physiotherapieunclassified